Explorations of Tolerant Trichoderma spp. as Plant Growth Promoter and Biocontrol Agent against Colletotrichum falcatum - Ziyaul Haque; Mohammed Shariq Iqbal; Ausaf Ahmad; Mohd Sajid Khan; Satarudra Prakash Singh; Jyoti Prakash (Journal of Pure and Applied Microbiology, 2020)
The present study was focused on microscopic and molecular characterization with growth optimization of two fungal isolates of Trichoderma spp. (TS) along with their antagonistic activities against Colletotrichum falcatum (CF) and plant growth promoter activity. The microscopic and molecular analysis (Internal transcribed spacer - ITS1 region of 18S rRNA) of these isolates revealed that the isolates were Trichoderma asperellum (MK937669) (TA) and Trichoderma viride (MK503705) (TV). The parameters for maximum growth were found to be in TA and TV in potato dextrose agar (PDA) and Sabouraud dextrose agar (SDA) for media components, 25˚C for temperature and for pH (TA 5.5 and TV 6.5) respectively. The antagonistic activity of TS was studied and it was found to be notable against CF (CF02 strain) with 77.666±4.509% and 72.666±7.094 % of inhibition by TA and TV respectively. As a plant growth promoter it was found that maximum Indole-3-acetic acid (IAA) production with 0.5% of L-tryptophan was with 120.308±5.256µg/mL by TA and 130.101±8.995µg/mL by TV. However, when phosphate solubilization (PS) was studied, it was found maximum at day 5 with 410.285±32.084µg/mL by TA and 459.126±38.629µg/mL by TV. When two-way ANOVA was applied it was also found to be significant with p value < 0.05. Overall, the isolated TS species can be rapidly and efficiently produced using the optimum conditions for effective management of CF with good plant growth promoter activty, thus serve as an eco-friendly approach for plant protection and yield increase, thereby economically useful for agricultural industry.